Respuesta :

Answer: x = 6

* = things that have changed or are being changed

Explanation:

1. rearrange terms

*4 4  +  3 *  =  5  +  2  +  2 0

*3x + 44* = 5x + 2 + 20

2. combine like terms

3 + 44 = *5x + 2* + 20

3 + 44 = *7x* + 20

3. Subtract  4 4  from both sides of the equation

3x + 44 = 7x + 20

3x + 44 *-44* = 7x + 20 *-44*

4. Simplify

(Subtract the numbers)

3x + *44 - 44* = 7x + 20 - 44

3x = 7x + 20 - 44

(Again)

3x = 7x + 20 *- 44*

3x = 7x - 24

5. Subtract  7  from both sides of the equation

3x = 7x - 24

3x *- 7x* = 7x - 24 *- 7x*

6.  Combine like terms

*3x - 7x* = 7x - 24 - 7x

*-4x* = 7x - 24 - 7x

(Again)

-4x = *7x* - 24 *- 7x*

-4x = - 24

7. Divide both sides of the equation by the same term

-4x = - 24

[tex]\frac{-4x}{*-4*} = \frac{-24}{*-4*}[/tex]

8. Simplify

(Cancel terms that are in both the numerator and denominator)

[tex]* \frac{-4x}{-4} * = \frac{-24}{-4}[/tex]

*x* = [tex]\frac{-24}{-4}[/tex]

(Divide the numbers)

x = [tex]\frac{-24}{-4}[/tex]

x = 6